2021
DOI: 10.1111/jocd.14347
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, split‐face study of topical timolol maleate 0.5% eye drops for the treatment of erythematotelangiectatic rosacea

Abstract: Rosacea is a chronic inflammatory cutaneous disease with varying prevalence. The pathophysiologic mechanisms include an interaction between genetic and environmental factors, neurovascular dysregulation, and increased immune response. These mechanisms lead to the main symptoms of inflammation, vasodilation, and angiogenesis. The classification of rosacea involves four subtypes designated as follows: subtype 1, erythematotelangiectatic; subtype 2, papulopustular; subtype 3, phymatous; subtype 4, ocular. Rosacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In another study, 16 patients with mild to moderate ETR were enrolled in a randomized, single-blind, placebo-controlled split-face study, where the side of the face treated with timolol maleate 0.5% eye drops applied with wet compresses every night for 28 days showed significant improvements in the Clinician Erythema Assessment (CEA) and a patient self-assessment (PSA). Although one case of local adverse reaction occurred, it resolved on its own [ 224 ]. However, a single-arm clinical study involving 58 patients with ETR and PPR found that although topical timolol 0.5% improved clinical parameters of rosacea, it did not reach statistical significance.…”
Section: Treatmentsmentioning
confidence: 99%
“…In another study, 16 patients with mild to moderate ETR were enrolled in a randomized, single-blind, placebo-controlled split-face study, where the side of the face treated with timolol maleate 0.5% eye drops applied with wet compresses every night for 28 days showed significant improvements in the Clinician Erythema Assessment (CEA) and a patient self-assessment (PSA). Although one case of local adverse reaction occurred, it resolved on its own [ 224 ]. However, a single-arm clinical study involving 58 patients with ETR and PPR found that although topical timolol 0.5% improved clinical parameters of rosacea, it did not reach statistical significance.…”
Section: Treatmentsmentioning
confidence: 99%